Assessment of selected food intake frequency in patients with type 1 diabetes treated with personal insulin pumps - Sabina Krzyżowska; Bartłomiej Matejko; Beata Kieć-Wilk; Magdalena Wilk; Maciej Małecki; Tomasz Klupa (National Institute of Public Health - National Institute of Hygiene, 2019)
Background. It has been established that in Type 1 Diabetes Mellitus (T1DM), regardless of the insulin therapy model used, diet and proper eating habits are still important in the treatment of the disease. The dietary intervention in these patients is aimed at maintaining proper body weight, obtaining target fasting and post meal blood glucose levels, optimizing lipid profiles. Objective. The aim of the study was to assess dietary habits in a homogeneous group of adults with T1DM treated with personal insulin pumps. Material and methods. The study included 141 adult patients (57% women) with type 1 diabetes treated with personal insulin pumps. The surveyed population was characterized by an average age of 25.8 ± 6.2 years, an average duration of diabetes 13.9 ± 6.9 years, and treatment with a personal pump for 8.2 ± 4.1 years and mean BMI 23.0 ± 2.8 g/m2. All were dwellers of south-eastern Poland. The validated KomPAN questionnaire was used to assess the frequency of consumption of individual food products. Results. The mean percentage of HbA1c in the study group was 7.3% [56 mmol/mol]. The mean total cholesterol level was 4.4 mmol/l, HDL - 1.7 mmol/l, LDL - 2.3 mmol/l and triglycerides - 0.8 mmol/l. In the multivariate regression model, no correlation was found between dietary quality parameters and metabolic compensation measured with HbA1c or lipidogram and the place of residence (village, small town, big city). However, there were differences in the quality of the diet depending on the sex. Women were characterized by higher index of a healthy diet (pHDI-10) (26.3 vs 21.4, p=0.005) and lower index of unhealthy diet (nHDI-14) (13.3 vs 18.6, p <0.001) than men. Conclusions. The results of this study clearly suggest, that despite good metabolic control, patients require more education on the choice of healthy product groups.